Development of E-Card Quartet Learning Media Based on The TGT to Improve Understanding of The History of The Birth of Pancasila In Pancasila Education For Seventh Grade Students at State Junior High School 7 in Kediri City - Wahyu Fajar Permadani; Nuruddin Hady; Didik Sukriono (FKIP - Universitas Riau, 2026)
This study was driven by the limited interest and understanding of students regarding the history of the birth of Pancasila, which had long been taught through conventional methods. To address this issue, the research developed and assessed the E-Card Quartet learning media based on the Team Games Tournament (TGT) model as a more interactive alternative. Using a Research and Development approach with the ADDIE model covering analysis, design, development, implementation, and evaluation the study involved 32 seventh-grade students at SMP Negeri 7 Kota Kediri. Data were collected through observation, tests, interviews, and documentation. The results indicated that the media achieved a high level of validity, with a material expert validation score of 92.5% and media expert scores of 88% and 85%. Its practicality was also confirmed through a 92% positive student response. The effectiveness of the media appeared in the significant improvement in learning outcomes, shown by an increase in the average score from 68.13 on the pre-test to 90 on the post-test. Overall, the TGT-based E-Card Quartet proved effective in enhancing students’ comprehension of the history of Pancasila’s birth.